Analisis Investasi Rumah Tinggal 2 Lantai Proyek Berdasarkan Metode NPV, IRR, BCR dan Cash Flow - Yoga Alvian Pratama; Amri Gunasti (CV. Akira Java BUlu, 2026)
The construction of a two-storey residential house requires a detailed cost estimation to ensure that the project is financially feasible. This study aims to analyze the investment value of the Adel House two-storey housing project based on the Bill of Quantity (RAB) data and cash flow evaluation. The research method used in this study is a quantitative descriptive method through documentation study using project budget plan data obtained from the Excel-based Bill of Quantity (RAB). The research stages include data collection, cost recapitulation, cash flow preparation, and financial feasibility analysis using Net Present Value (NPV), Internal Rate of Return (IRR), and Benefit Cost Ratio (BCR) methods. The cost data include several main work components such as preparation works, earthworks, reinforced concrete works, wall works, roofing and ceiling works, floor and wall finishing works, aluminum and steel works, painting works, and mechanical-electrical-plumbing (MEP) works. The total direct construction cost of the project is IDR 256,070,300, with an additional calculated amount leading to a total project cost of approximately IDR 284,238,000. The results of the financial feasibility analysis indicate that investment feasibility can be determined by comparing the present value of benefits and costs over the project life cycle. A project is considered financially feasible if the NPV is positive, the IRR exceeds the discount rate, and the BCR value is greater than 1. This study provides a financial assessment framework for residential construction projects based on cost planning and economic engineering principles.